A clash of kings - Martin, George R. R. (New York : Bantam Books, 2012)
Six separate factions vie for control of the realm of the late Lord Eddard Stark, while an ancient form of magic, an everlasting winter, and an unearthly army threaten to return.
Reprint. Originally published: 1999.
Sequel to: A game of thrones.
"Now the ... HBO series Game of Thrones"--Cover.
Keywords: Imaginary places -- Fiction; Imaginary wars and battles -- Fiction; Civil war -- Fiction; Kings and rulers -- Fiction; Civil war; Imaginary places; Imaginary wars and battles; Kings and rulers; Fiction